Linking Regional Knowledge Laboratory and Growth of smes – Empirical Investigation in Southern Region of Poland - Kosała, Małgorzata; Wach, Krzysztof (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2015)
The regional knowledge laboratory, being a part of the regional innovation system, impacts the regional innovation potential of regional firms, especially SMEs. Diffusion of innovations consists of the penetration of innovative solutions into the whole social and economic system, the result of which is a change in its functioning and overall development. The process of diffusion of innovations in a sense forces the innovativeness of the competing enterprises by necessitating their adaptation to the changing conditions of the environment. Diffusion of innovations is a determinant of the growth and development of enterprises, especially those of the SME sector. The paper is an attempt to empirically verifythe dependence between the development of small and medium-sized enterprises and the innovative potential of the studied region. Due to utilitarian reasons, the region was defined in accordance with the European statistical terminology (NUTS1 - regions in the total number of 6) as the area of two administration regions (NUTS2 - voivodeships in the total number of 16): małopolskie and śląskie, which makes of one statistical regional (PL2 - Southern Region of Poland). The empirical material was based on a random sample of 109 micro, small and medium-sized enterprises located in the studied region. With the use of computer statistical tools, the hypothesis made in the paper was confirmed, namely that the level of commercialization of knowledge and the transfer of technology in the studied region influences the development of small and medium-sized enterprises.